TMS‐measures of cortical excitability are abnormal in amyloid‐positive MCI, relate to amyloid burden, and predict faster cognitive decline: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Buss, Stephanie S.; Macone, Joanna; Li, Gongri; McDonald, Katherin; Shafi, Mouhsin; Donohoe, Kevin; Press, Daniel Z.; Pascual‐Leone, Alvaro; Fried, Peter J.
Abstract: Background: Alzheimer's disease (AD) is associated with increased cortical excitability, including a risk of seizures and epileptiform discharges. Transcranial magnetic stimulation (TMS) can be used to index cortical excitability non‐invasively, and previous studies have revealed increased TMS excitability measures in AD. However, it is not yet known if TMS shows increased cortical excitability in amyloid‐β positive mild cognitive impairment (Aβ+ MCI), how TMS excitability relates to other AD biomarkers, or the extent to which cortical excitability may predict disease progression. Method: TMS was applied to left motor cortex in 18 participants with Aβ+ MCI (aged 70±8.9, 9 females). Resting motor threshold (RMT) was measured as the minimum TMS intensity required to elicit a motor evoked potential on 5/10 trials. The primary analyses tested if RMT differed between Aβ+ MCI participants and a cohort of 36 older healthy controls (OHC; aged 63±9.7, 17 females). Separate linear models in Aβ+ MCI tested the relationship of RMT with hippocampal volume, Aβ burden on [ 18 F]Florbetapir PET, and the Clinical Dementia Rating – Sum of Boxes (CDR‐SB). CDR‐SB was reassessed after 1‐2 years follow‐up, and a CDR‐SB Change Score was calculated to measure cognitive decline. The relationship with RMT and CDR‐SB Change Score was tested using a simple linear regression. Result: The primary linear model controlling for age, gender, and scalp‐to‐cortex distance (SCD) showed a between‐group difference in RMT (B=3.62, p=0.023, Figure 1), with Aβ+ MCI showing lower RMT reflecting higher levels of cortical excitability. The covariate of SCD (B=1.92, p<0.001) was also significant. Secondary models with the same covariates showed that lower RMT was related to greater Aβ burden (B=‐0.43, p=0.016), but not hippocampal volume or CDR‐SB. In the subgroup of 10 Aβ+ MCI participants with longitudinal follow‐up, lower RMT predicted of worsening cognition on CDR‐SB Change Score (R=0.74, p=0.015, Figure 2). Conclusion: Increased cortical excitability is found in Aβ+ MCI, is related to amyloid burden, and appears to predict greater longitudinal cognitive decline. TMS measures of cortical excitability may be useful as measures of target engagement for future therapies aimed at delaying disease progression in the early symptomatic stages of AD.